Health and safety: real time detection of Bukholderia pseudomallei and pathogenic leptospira spp using a new portable amplification diagnostics system - Aziah, Ismail (Pusat Pengajian Sains Perubatan Universiti Sains Malaysia, 2017)
Burkholderia pseudoma/lei is the causative agent of melioidosis, an infectious disease with multifarious manifestations. The gold standard for diagnosis is the culture that requires 2-7 days to obtain a result hindering successful treatment of the patients. Leptospirosis is a widespread infection of human and animals (Rao eta/., 2003), and locally it assumes considerable importance as a public health and economic problem. Early detection of Leptospira spp. is an essential requirement in its management practice. Microscopic agglutination test (MAT) is the gold standard with high sensitivity that detects the group-specific antibodies but it is complex due to the requirement of maintaining strains or isolates for the preparation of live antigens. The microscopy method using dark field microscope is reported as easier for visualizing leptospiras in blood and urine but it lacks sensitivity. As an alternative to these methods, Orf2 and lip32L genes were used to develop the DNA-based diagnostics and detect for the presence of Burkho/deria pseudomallei and pathogenic Leptospira spp. Two sets of primers were designed and used to optimize the amplification of the two specific regions of the desired genes. The amplification was successfully developed with the detection limit of detection limit of the orf2 and lipl32 amplification 10 pg/~1 and 26.75 pg/~1 respectively. Both tests showed the amplification of the two genes are specific and could be used to further verification and evaluation of the test. The findings suggested that the verification of the specific primers for both Burkho/deria pseudomallei and pathogenic Leptospira spp. was successful. A probebased amplification system will be further optimised with the presence of heating system as a complete portable system for the preparedness of the bacterial detection during the flood situation.